Estimates of eligibility for antiretroviral treatment (ART) and projected ART impact on AIDS mortality among South African educators - Thomas M Rehle; Olive Shisana (Taylor & Francis Group, 2005)
The study assessed the proportion of HIV-infected educators that need antiretroviral treatment (ART) according to current criteria, and estimated the impact of ART on AIDS mortality by modelling scenarios with and without access to ART. Specimens for HIV testing were obtained from 17 088 educators and a sub-sample of 444 venous blood specimens from HIV-positive educators was selected for a CD4 cell count analysis. The Spectrum model package was used for estimating AIDS-associated mortality and projecting the impact of ART scenarios. The results of the CD4 cell count analysis in the HIV-positive educator study population showed that 8% had fewer than 100, 22% fewer than 200, 52% fewer than 350, and 72% fewer than 500 CD4 cells/mm3. Based on the proportion of HIV-positive educators with a CD4 cell count < 200 cells/mm3 we estimated that in 2005 approximately 10 700 educators would need ART according to current SA government guidelines. For the baseline scenario without ART the number of AIDS deaths among HIV-infected educators was projected to increase from 1 992 deaths in 2000 to 5 260 in 2010. The number of projected AIDS deaths in the educator study population was estimated to be 4 414 in 2005, with almost 50% of the AIDS deaths occurring in the 35 - 44 age group.The estimates suggest that in 2005 9.1% of the HIV-infected educators, or 1.2% of the total educator population, will be dying of AIDS. By 2010, a reduction of almost 50% in AIDS deaths was estimated for the treatment scenario with 90% ART coverage, compared with the baseline scenario without treatment. The ART impact scenarios illustrate that a relatively high ART coverage would be needed to ensure a substantial impact of ART on HIV/AIDS-associated mortality.